2023
DOI: 10.3390/biom13101430
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Adhesion and Migration via Microtubule Cytoskeleton Organization, Cell Polarity, and Phosphoinositide Signaling

Narendra Thapa,
Tianmu Wen,
Vincent L. Cryns
et al.

Abstract: The capacity for cancer cells to metastasize to distant organs depends on their ability to execute the carefully choreographed processes of cell adhesion and migration. As most human cancers are of epithelial origin (carcinoma), the transcriptional downregulation of adherent/tight junction proteins (e.g., E-cadherin, Claudin and Occludin) with the concomitant gain of adhesive and migratory phenotypes has been extensively studied. Most research and reviews on cell adhesion and migration focus on the actin cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Although polystyrenesulfonate-modified nanoparticles did not affect the cell proliferation and differentiation capability of MSCs, a study has previously shown that sodium tanshinone IIA sulfonate inhibited migration and invasion in human cells . The migration ability declined probably due to altered actin cytoskeleton, cell stiffness, cell adhesion, and cell morphology, as well as the generation of fewer stress fibers and higher aggregate formation that impact the cell motility and traction force. , Nevertheless, the impact of these functionalized silica nanoparticles on the migration ability and cytoskeleton remodeling was subtle.…”
Section: Resultsmentioning
confidence: 99%
“…Although polystyrenesulfonate-modified nanoparticles did not affect the cell proliferation and differentiation capability of MSCs, a study has previously shown that sodium tanshinone IIA sulfonate inhibited migration and invasion in human cells . The migration ability declined probably due to altered actin cytoskeleton, cell stiffness, cell adhesion, and cell morphology, as well as the generation of fewer stress fibers and higher aggregate formation that impact the cell motility and traction force. , Nevertheless, the impact of these functionalized silica nanoparticles on the migration ability and cytoskeleton remodeling was subtle.…”
Section: Resultsmentioning
confidence: 99%
“…They were fine-tuned to meet the needs of cells and tissues. The ability of microtubules to regulate cell migration through coordinated interactions between polymerization/depolymerization and adhesion patch assembly/disassembly, as well as their ability to regulate Rho-GTPase signaling for actin contractility, suggests that the changes in microtubule motility could account for alterations in the migratory and contractile capacities of cells [ 41 , 42 ]. Clusters 2 and 5 were both biological processes that affected the extracellular space but the focus was different; cluster 2 primarily affected integrin signaling and the differentiation and growth of VSMCs, and cluster 5 focused on extracellular matrix proteins and cytoskeletal processes that regulated cellular behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Structural chromatin organization also plays a significant role in cellular migration (Gerlitz, 2020). In addition, numerous biochemical molecules and other physiological processes are involved in the directional movement of cells, including PI3K (Inoue and Meyer, 2008), focal adhesion proteins (Artemenko et al, 2014), actin-binding proteins (Lee and Dominguez, 2010), PLEKHG3 (Nguyen et al, 2016), p21-activated kinases (Kumar et al, 2009), SCAR/WAVE proteins (Pollitt and Insall, 2009), Arp2/3 complexes (Swaney and Li, 2016), mitogen-activated protein kinases (Huang et al, 2004), actin-capping protein (Ogienko et al, 2013), WASP family proteins (Veltman and Insall, 2010), phosphoinositide lipid molecules (Ling et al, 2006; Kakar et al, 2023; Thapa et al, 2023), TORC2/PKB pathway (Cai et al, 2010), and the Nck family of adaptor proteins (Rivera et al, 2006), among others.…”
Section: Introductionmentioning
confidence: 99%

Systemic migrations in enucleated cells

De la Fuente,
Carrasco-Pujante,
Camino-Pontes
et al. 2024
Preprint